Improved electromagnetic wave absorbing performance of PDCs-SiCN(Ni) fibers with different nickel content. Issue 16 (15th August 2022) - Lu, Junbin; Feng, Yurun; Liu, Jie; Liu, Chunmiao; Tong, Yanchun; Wu, Shigang; Sun, Haibin; Gong, Hongyu; Guo, Xue
Abstract: The PDCs (polymer-derived ceramics)-SiCN(Ni) fibers with multiple loss mechanisms were prepared by electrospinning. Influenced by the in-situ formed CNTs and Ni2 Si at the high treatment temperature, the impedance matching performance of fibers was enhanced obviously. In addition, the electromagnetic wave (EMW) absorbing performance was further improved by unique one-dimensional structure of fibers, interfacial polarization, dipole polarization and magnetic loss. Because of good impedance matching and multiple losses, fibers possessed admirable EMW characteristic with strong absorbing ability of the minimum reflection loss (RL) reaching −44.88 dB and the widest effective absorption band (EAB) reaching 4.8 GHz (13.2–18 GHz) at 1.42 mm. Hence, SiCN(Ni) ceramics prepared had a wide application in the field of electromagnetic absorption.